Entrepreneurial Readiness in Health Science Education: The Roles of Mental Health and Psychological Resilience Using Structural Equation Modelling - Sulistiawan, Andika; Idrus, Ali; Firman; Noerjoedianto , Dwi; Maryani , Anis Tatik; Subandi , Andi; Sulistiyo , Urip; Saputra , Endarman (International Journal of Learning Reformation in Elementary Education, 2026)
This study examined the role of psychological resilience and mental health in predicting entrepreneurial readiness among health students. Using a cross-sectional explanatory design, 412 students were recruited through purposive sampling from a faculty of health sciences. Data were collected using the Connor-Davidson Resilience Scale (CD-RISC), the Depression Anxiety Stress Scales (DASS-21), and an entrepreneurial readiness questionnaire. Data analysis was conducted using Structural Equation Modeling (SEM) with model fit indices. The results showed that resilience had a strong and significant direct effect on entrepreneurial readiness (β = 0.929; p < 0.001) and on mental health (β = 0.992; p < 0.001). In contrast, mental health did not show a significant direct effect on entrepreneurial readiness (β = 0.062; p = 0.528). These findings highlight resilience as a central psychological competence that not only enhances well-being but also plays a crucial role in strengthening entrepreneurial readiness among health students. Therefore, strengthening psychological resilience through campus-based training programs and interventions may serve as a relevant strategy to prepare a more resilient generation of health students who are better equipped to face future challenges in both employment and entrepreneurship.